Makna lirik lagu cerita rakyat Karya Fiersa Besari sebagai media kritik sosial - Aloysia, Dian Andriana Martiani Lova; Purnamasari, Hetty; Utami, Sri (Aksara: Jurnal Bahasa dan Sastra, 2023)
Song lyric is one of the verbal communication media that has a number of meanings. This study aims to find out the meaning of the lyrics of Cerita Rakyat through a semiotic approach and to find out what social criticism that contained in the song lyrics. The approach that used in this study is a semiotic theory approach of Roland Barthes. The method that used in this study is an interpretative qualitative research. The data source is a song by Fiersa Besari entitled Cerita Rakyat as a medium of social criticism. The data are song lyrics of Cerita Rakyat by Fiersa Besari. The data collection technique used is a literature study and observation made on the song of Cerita Rakyat. The data analysis technique used is Roland Barthes semiotic analysis tool where the aspects studied include the denotation level, connotation level, and social criticism contained in the lyrics of Cerita Rakyat. The results showed that the song lyrics by Fiersa Besari entitled Cerita Rakyat contain words with meanings of denotation, connotation, and also contain social criticism as a form of expression for what is felt. Keywords: Song Lyrics, Cerita Rakyat, Social Criticism, Semiotics.